(untitled) (Research, Society and Development, 2024)
Rapid maxillary expansion (RME) in adult patients is a crucial topic in contemporary orthodontics, offering new perspectives and solutions to challenging cases of skeletal and dental discrepancies. This study aims to examine the effectiveness of MARPE and mini-implant assisted rapid maxillary expansion, highlighting the benefits and clinical considerations involved in this innovative procedure. Rapid maxillary expansion is an established technique in orthodontics for correcting posterior crossbite problems and narrow jaws. Clinical studies show that the use of mini-implants as skeletal anchorage provides a more controlled and stable expansion of the maxilla, minimizing side effects and improving respiratory function and periodontal health. In addition to reducing treatment time, interdisciplinary collaboration between orthodontists and dental surgeons is essential to maximize the effects.